Viromics-based precision diagnosis of reproductive abnormalities in cows reveals a reassortant Akabane disease virus - Yue Sun; Ru Zhang; Huiyu Wang; Zheng Sun; Le Yi; Changchun Tu; Yanling Yang; Biao He (BMC Veterinary Research)
Abstract Background At the end of 2021, an epidemic of reproductive abnormalities in cows occurred in Jilin Province, China, posing an urgent need for a rapid diagnosis. Results To identify the cause of the disease, a total of 172 samples were collected from 21 dead calves and 45 aborting or pregnant cows in 10 farms across the province. Routine PCR or RT-PCR detection did not find any common abortion-related agents. We then employed the viromics-based precision diagnosis method to analyze these samples, and the read-based annotation showed signals of an Akabane disease virus (AKAV) in some libraries. To further identify the virus, nested RT-PCR detection revealed that 52.3% (11/21) of dead calves and 26.6% (12/45) of cows were positive for the virus. Phylogenetic analysis of the partial fragments showed that the S segment of the virus was 100% identical to the Chinese strain TJ2016, but its M and L segments shared 94.3% and 96.5% identities with an Israeli strain. Conclusions The viromic and molecular results suggested that these animals were infected with a reassortant AKAV. Coupled with the clinical signs, the virus should be responsible for the epizootic, highlighting that molecular and serological surveys of the virus in cows during early pregnancy, as well as ecological investigation in its arthropod vectors, are necessary.